Respiração do feijão durante o armazenamento sob condições controladas e com diferentes teores de água - (:unkn) unknown (Universidade Estadual de Goiás, 2019)
The objective of this study was to evaluate the respiratory rate and dry matter loss of bean grains atdifferent water contents and storage temperatures. The experiments were carried out at the Laboratoryof Drying and Storage of Vegetable Products of the State University of Goiás, located at the CampusCCET - Henrique Santillo, Anápolis - GO. Six kilos of beans (Phaseolus vulgaris L), cultivar BRS MGENERGE, were obtained from another experiment in (Emater Anápolis). Six kilos of common beangrains were harvested with field moisture, and in sequence were dried using artificial ventilation withnatural ventilation (using solar and wind energy) until reaching water contents of 21, 18, 15 and 12% buSamples were taken to B.O.D type chambers being stored at temperatures of 25 and 30 ° C. For 90 days,with a seven day interval, the samples were taken to a multi-channel gas analyzer which quantified theCO 2 and O 2 contents, as well as the respiratory rate. For the loss of dry matter, the samples wereweighed in intervals of seven days, and later, calculated by means of formula. The experiment wasdeveloped in a randomized design with subdivided plot with factorial in the plot. The interaction of thetreatments, Water contents (21, 18, 15 and 12% bu) and Storage temperature (25 and 35 ° C) in theplot, with three replications, totaling 24 observations, and Time factor in the subplot, with weeklyevaluations during 90 days of storage, totaling 13 analyzes. After data collection, the analysis ofvariance was performed by the F test at 5% probability and, when significant, were submitted toregression analysis for quantitative factors and Tukey averages comparison test for qualitative factors. Inthe artificial drying by natural ventilation were reached the contents of 12.56; 15,30; 18.08 and 21.46%b.u. The highest water contents (18.08 and 21.46% b.u) gained dry mass up to the fifth week of storage.The water content of 15.30% b.u obtained polynomial behavior, and it was verified that it did notpresent considerable losses throughout the storage. This same fact occurred for the water content of12.56%. All water contents in the first week of storage for both temperatures obtained 0.02% drymatter loss in common bean grains of BRSMG REALCE. The CO2 production was higher for the watercontent of 21.46% b.u at the temperature of 30 ° C with a value of 254.23 mg CO2. The O 2consumption presented normality in the data, and its coefficient of variation was of 47.09, consideredvery high. The water and temperature content best suited to a safe storage for common bean grains ofBRSMG REALCE is 12.56% b.u and 25 ° C, respectively.
Respiration rate and dry matter loss of beans with different moisture contents and storage temperatures
Keywords: Dióxido de Carbono; BRSMG realce; Breathing; Carbon dioxide; BRSMG enhancement; CIENCIAS AGRARIAS::ENGENHARIA AGRICOLA